Caregiver Experiences of Supporting Adults with Intellectual Disabilities in Pain. Issue 2 (9th June 2014) - Findlay, Laura; Williams, Amanda C. de C.; Baum, Sandra; Scior, Katrina
<x xml:space="preserve">Abstract</x> Background Caregivers have an intimate knowledge of the individuals they care for and are therefore an important source of information on pain experiences. They are often relied upon to recognize pain‐related behaviours and report them, but little is known as to how they experience their role. Methods Information was collected from 11 caregivers using semi‐structured interviews about their experiences of caring for adults with intellectual disabilities who were suspected or definitely in pain. Transcripts were analysed using Interpretative Phenomenological Analysis. Results Six superordinate themes were identified from participants' experiences: suffering in silence; searching for meaning to explain the complaint; knowledge and skills needed to recognize and manage pain; perceptions of the pain experience; acting to try and reduce pain; and the emotional impact of pain. Conclusions There seems an art to detect pain using existing skills and knowledge of the individual's ways of expressing pain. Despite best efforts, recognizing and treating pain was experienced as complex and ambiguous. Some caregivers described a negative emotional impact and dissatisfaction with the management of pain by health care services.